Title: Impact of brand experience on brand love and brand loyalty --in an empirical context of the gaming industry - YANG, Z. (2020)
Abstract Objectives – Existing literature on brand experience and brand loyalty tends to ignore the role of mediating effects in the relationships between brand experience and brand loyalty. Moreover, the literature has not examined the relational dimensions of brand experience in the gaming industry as a service context. Hence, the major objectives of this study are to examine the relationship among brand experience, brand love and brand loyalty in the gaming industry as a service context. This study aims to propose a model where brand experience could both directly impact brand loyalty, and indirectly impact brand loyalty via the mediation effect of brand love. Especially, this dissertation examines three issues: (1) Is the relational dimension valid in the specific industrial context of gaming? (2) Do individual brand experience dimensions (i.e. sensory, affective, and relational) vary in their effect of impact brand love and brand loyalty? (3) Is brand love playing the role of a mediator between the relationship of brand experience and brand loyalty? Methodology – A quantitative research method was conducted. A five-point Likert scale questionnaire as a survey instrument was designed applying existing measurement scales established by previous scholars. 202 valid samples on gaming brands were collected in total from voluntary participants who confirmed they love playing video games and have favourite gaming brands and analyzed using the confirmatory factor analysis (CFA) method. Findings – (1) brand experience as a whole construct has a significant positive impact on brand love. While sensory, affective and relational experiences are all important drivers of brand love, sensory experience is the most important antecedent compared to affective and relational ones. (2) brand experience as a whole construct has a significant positive impact on brand loyalty. Again, sensory experience has a direct impact on brand loyalty, however, affective and relational ones do not. (3) brand love has a significant positive impact on brand loyalty. (4) brand love has a partial mediating effect between brand experience and brand loyalty. Specifically, while it has a partial mediating effect between sensory experience and brand loyalty, it serves as a full mediator both in the relationship of affective and relational experience with brand loyalty. Contributions – It identified brand love’s mediation role in the relation of brand experience (sensory, affective, and relational) and brand loyalty, particularly in the gaming industry, and thus contributes to a deeper-level interpretation towards the complexity of the brand experience construct by empirically studying experience dimensions as individual variables, revealing the fact that the three dimensions vary in their ability to impact brand love and brand loyalty. Sensory experience is the strongest factor of inducing brand love and brand loyalty, while affective and relational experience can only impact on brand loyalty via brand love. Keywords: Experience marketing, Brand experience, Brand experience dimensions, Brand loyalty, Brand love, Confirmatory factor analysis (CFA), The service context, The gaming industry Paper type: Master Degree Dissertation